EVALUASI PENILAIAN KINERJA APARATUR SIPIL NEGARA PADA SEKRETARIAT DAERAH KABUPATEN MUNA - MR Sumikro; Juharsah Juharsah; Sri Wiyati Mahrani; Hartini Hartini; Nuryamin Budi; Farhan Ramadhani Istianandar (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to evaluate the performance assessments of the state’s civil personnel assessment on muna district secretariat using a benchmark for the performance assessment system. The study discussed the implementatioan of the performance assessment and its use for the muna district secretariat organitation. The Study took the key 10 civil personnel informants on the secretary of muna district using a qualitative approach based on case studies. The Type and data sources used were the archives and interview reports and observation in the secretariat of muna district. Study have shown that governmental regulation as measures in assessment of civil personnel have not been followed. The performance assessment doesn’t show optimal results. Application of the job performance assessment rules become just a formality. The performance assessment system that is a quantifying tool to see the work of employees become objective. Then for the results of performance assessment it is not a guarantee for a counttry’s civil personnel to gain position and promotion. Performance assessment as measures have not been deemed important because in the end the assessment results could not get a position even if country’s civil personnel had a good performance.